EPISTEMOLOGI PENDIDIKAN PANCASILA DI ERA DISRUPSI: KONSEP PENGETAHUAN BENAR DALAM TES KEMAMPUAN AKADEMIK PANCASILA 2026 SERTA IMPLIKASINYA TERHADAP IDENTITAS GLOBAL CITIZEN - Az Zahra, Putri Salma; Diva Fitria Kusumawardani; Gilang Aditya Nugroho; Hanum Kholifah Ramadhani; Intan Amalia Putri; Muhammad Hafis Hari Alfarizi (Universitas Nias Raya, 2026)
Advances in information technology in this era of disruption are transforming the way society acquires and evaluates the truth of knowledge. This situation demands that civic education be grounded in a strong epistemological foundation, particularly in Pancasila education, which emphasizes not only cognitive aspects but also moral and national values amid globalization and the post-truth phenomenon. This study aims to analyze the concept of